PENGARUH BUDAYA ORGANISASI TERHADAP LOYALITAS KARYAWAN DI FAVEHOTEL OLO PADANG - Sofia Ayunda; Arif Adrian; Nidia Wulansari (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2022)
This study aims to determine the effect of organizational culture (X) on employee loyalty (Y) at FaveHotel Olo Padang. Data was obtained by distributing questionnaires. This study obtained the results of research where the variables of organizational culture and employee loyalty are in the good category. From the results of the simple regression test, the regression coefficient equation is 0.288 with a sig value. 0.002 < 0.05, meaning that 1 unit of organizational culture will increase by 0.288 units of employee loyalty. And obtained the value of R Square 0.227. This means that there is an influence of organizational culture on employee loyalty where the value is 22.75% and 77.3% is influenced by other factors.